Is the export success of SMEs related to the financial management? The case of exporting SMEs in Costa Rica - Martínez Villavicencio, José (2018)
According to economic indicators, SMEs have become an essential part of the Costa Rican economy. However, the Export Performance Index (IPE) has shown a decline of the highly successful exporting companies, and an increase of the ones cataloged as unsuccessful. For that reason, in this study we analyze and measure if the implementation of financial models and financial order can influence a proper development and the achievement of objectives of exporting SMEs established in Costa Rica. In accordance to this purpose, a mixed approach was used, for which a hypothesis “the greater the financial order in Costa Rican SMEs exporting, more export success” was established. An analysis of Spearman correlation and a Student's t-test comparison of averages were used to analyze the results. From a sample of 302 companies, it was concluded that a frequent execution of financial activities and financial order activities on SMEs is not necessarily associated with a high IDE. This study is aim to collaborate with future academic research agendas on SMEs topics.